The role of Cholpon’s translation skills in Uzbek translation studies - Karimova, Ugiloy (The Lingua Spectrum, 2026)
This article provides a scholarly analysis of the translation work of Abdulhamid Sulaymon ugli Chulpon, a prominent figure in twentieth-century Uzbek literature, as well as his contribution to the development of Uzbek translation studies and his principles of literary translation. The study examines Chulpon’s approach to translating works of world literature into Uzbek, his skill in maintaining harmony between the original text and the translation, his views on translation theory, and his role in the formation of the Uzbek school of literary translation. The analysis demonstrates that Chulpon’s translations enriched national literature in terms of genre and style and played a crucial role in shaping the theoretical and practical foundations of Uzbek translation studies.